The Effectiveness of Synchronous and Asynchronous for Online Learning at Vocational High School - Wahyuni, Fitri (CV. Rayyan Dwi Bharata, 2023)
The goal of this study is to characterize the implementation of the online teaching and learning process (Synchronous and Asynchronous learning), including supportive and barrier elements, students' experiences with online learning, and future expectations for participation. During the COVID-19 epidemic, students are after completing the process of introducing online teaching and learning. The investigation was conducted out at SMK Negeri 1 Tebing Tinggi, which is located in Tebing Tinggi. This study uses qualitative methodologies in its investigation. Teachers from SMK Negeri 1 Tebing Tinggi were employed as participants in this study. Semi-regular inquiries and replies, as well as taking images and assessing field outcomes, were utilized to report data. The COVID-19 epidemic has had a significant impact on education, particularly the teaching and learning process; the implementation, which was formerly done face-to-face, has now been switched to an online teaching and learning process (Synchronous learning and Asynchronous learning). The availability of modern devices such as computers and cell-phones are as well as data bundles and reliable internet connections. There are also certain barriers for instructors in implementing the online teaching and learning process, such as numerous complaints about acquiring internet quotas, and students who are more inclined or hooked to using smartphones for entertainment than for doing homework. It is believed that through studying in this manner, children would be able to practice responsibility and extend their understanding of how to use existing technologies in the future.